Association between hospital community services and county population health in the USA. (27th January 2018) - Apatu, Emma; Hamadi, Hanadi; Abrams, Jasmine A; Metzger, Isha W; Spaulding, Aaron
Abstract: Objectives: Little research has utilized population level data to test the association between community health outcomes and (i) hospital-sponsored community services that facilitate access to care and (ii) hospital-sponsored community building services in the USA. Therefore, the purpose of this study was to examine these relationships. Methods: A secondary data analysis of the 2016 County Health Rankings and American Hospital Association databases was conducted via zero-truncated negative Binomial regression. Results: Findings indicate a statistically significant difference between the number of community healthcare access services and community building services with county's rank of health behavior. However, no statistically significant differences were found between the number of community healthcare access services and community building services with county rankings of length of life, quality of life or clinical care. Conclusions: Our findings suggest that quality measures of services may play a more important role in community health improvement and that there is opportunity for hospitals to revamp the way in which community health needs assessments are conducted. Additional federal action is needed to standardize hospital sponsored community health service data reporting so that practitioners, hospital administrators and researchers can more specifically define hospitals' role in public health protection in the USA.